Role of the multiple telomeric repeat arrays in integration, persistence, and efficacy of the commercial CVI988 vaccine - Luca D. Bertzbach; Yu You; Tereza Vychodil; Ahmed Kheimar; Lisa Kossak; Mohammad A. Sabsabi; Andelé M. Conradie; Benedikt B. Kaufer (mSphere)
ABSTRACT Marek’s disease virus (MDV) is a highly oncogenic alphaherpesvirus that causes fatal T cell lymphomas in chickens. Oncogenic MDV strains can integrate their genome into the host telomeres of latently infected and tumor cells. This integration process is facilitated by telomeric repeat arrays (TMR) present at the ends of the MDV genome, which consist of the hexanucleotide (TTAGGG)n that is identical to host telomere sequences. In addition, integration of the virus genome is crucial for the development of lymphomas. Live-attenuated vaccines play a vital role in protecting chickens against this deadly disease, yet our understanding of their biology remains limited. Intriguingly, the commercial gold standard MDV vaccine, the live-attenuated MDV strain CVI988, also possesses TMR at the ends of its genome. In this study, we investigated the role of the multiple TMR arrays (mTMR) in vaccine virus integration, latency, reactivation, and protection against very virulent MDV. Our data revealed that the mTMR present in CVI988 are important for virus genome integration and maintenance in latently infected cells in vitro. In addition, virus latency, reactivation, and vaccine efficacy were reduced in an mTMR deleted mutant compared to the wild-type vaccine. These results provide valuable insights into the biology of this important vaccine virus and shed light on the roles of the mTMR in vaccine integration, latency, and protection against very virulent MDV.IMPORTANCEMarek’s disease virus (MDV) is an oncogenic herpesvirus and causes lethal lymphomas in chickens. The gold standard vaccine is the live-attenuated MDV strain CVI988 (a.k.a. Rispens). CVI988 is extensively used in chickens worldwide due to its high efficacy in preventing disease and lymphomas. The CVI988 vaccine harbors telomere arrays (TMR) at the ends of its genome. TMR facilitate genome integration of oncogenic MDV strains into the host telomeres. This study provides critical insights into the biology of the widely used MDV vaccine strain CVI988, demonstrating the crucial role of mTMR in viral genome integration, latency, and protection against very virulent MDV. Furthermore, our findings enhance the understanding of MDV vaccine biology and may guide future strategies to improve Marek’s disease control.